1976
DOI: 10.2466/pr0.1976.38.2.359
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Peabody Picture Vocabulary in Estimating WISC Scores for Delinquents

Abstract: IQs on the Peabody Picture Vocabulary Test for 106 males 13 to 16 yr. and of lower class status were related to WISC IQs (assessed by student examiners) in three different ranges (80–89, 70–79, Below 70) as a function of race. Both group and individual results were consistent with previous data showing the Peabody scale generally overestimates the IQs of retarded subjects. The present results, however, also indicate that the Peabody tended to underestimate the IQs of 34 “Dull Normal” subjects. Thus, there appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The substantial loadings of the PPVT-B IQ on the two main factors in this study suggest that the PPVT adds little to the knowledge gained from the WISC-R. Although the correlation between the PPVT-B IQ and the WISC-R Full Scale IQ is rather high, studies using other than correlational designs indicated that the PPVT IQ should not be used as an estimate of the WISC-R IQ (see, e.g., Condit et al, 1976).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…The substantial loadings of the PPVT-B IQ on the two main factors in this study suggest that the PPVT adds little to the knowledge gained from the WISC-R. Although the correlation between the PPVT-B IQ and the WISC-R Full Scale IQ is rather high, studies using other than correlational designs indicated that the PPVT IQ should not be used as an estimate of the WISC-R IQ (see, e.g., Condit et al, 1976).…”
mentioning
confidence: 76%
“…Other purposes were to investigate the intercorrelations among the Peabody Picture Vocabulary Test (PPVT) IQ and the WISC-R subtest and summary scores, and to determine whether the PPVT is adding sufficient information to an intellectual assessment battery. The usefulness of the PPVT for predicting Wechsler Intelligence Scale for Children or WISC-R IQs is questionable (Appelbaum & Tuma, 1977;Condit, Lewandowski, & Saccuzzo, 1976).…”
mentioning
confidence: 99%
“…Hornstein and Mosley may have failed to achieve a significant interaction due to limitations of their methodology in making fine group discriminations. Their use of the Peabody Picture Vocabulary Test (PPVT) to discriminate among levels of retardation is questionable (Condit, Lewandowski, & Saccuzzo, 1976). Furthermore, as Galbraith and Gliddon (1972) and Miller, Saccuzzo, & Braff (1979) have shown, a pattern overlapping mask is far more discriminating than the procedure employed by Hornstein and Mosley.…”
mentioning
confidence: 99%
“…Hornstein and Mosley may have failed to achieve a significant interaction due to limitations of their methodology in making fine group discriminations. Their use of the Peabody Picture Vocabulary Test (PPVT) to discriminate among levels of retardation is questionable (Condit, Lewandowski, & Saccuzzo, 1976). Furthermore, as Galbraith and Gliddon (1972) and Miller, Saccuzzo, & Braff (1979) Relying on a two-factor theory of visual masking (Spencer & Shuntich, 1970), the critics claimed that i/ Turvey (1973) applies, then the mechanism of masking may have changed from integration to interruption differentially across groups.…”
mentioning
confidence: 99%